Allosteric Pathway Connects Zn(Ii) Loss from sod1 to Known Pathogenic Mechanisms - Dominguez-Caru, M (ELSEVIER, 2025)
Cu,Zn superoxide dismutase (SOD1) is one of the proteins with mutations linked to hereditary forms of the amyotrophic lateral sclerosis neurodegenerative disorder. The protein is known for its enzymatic activity, but it has been shown to also have regulatory functions, which could be related to its pathogenic potential. Seemingly unrelated to its regulatory roles, the most important hypothesis on SOD1 pathogenicity is related to misfolding of the protein, specifically centered on the region corresponding to its residues 28-38. The present work explores the structural and dynamical effect of Zn(II) removal from SOD1, which is known to influence its regulatory roles, with coarse-grained simulations of 450 mu s per system. In agreement with experiment, we see an increased solvent exposure of the regulatory region (residues 5-18). We also see an increased solvent exposure of the misfolding-critical 28-38 region. We unveil the mechanism and interactions connecting Zn(II) loss, and solvent exposure of both regions. The present work allows for an unified understanding of two different pathogenic mechanisms of SOD1.